Balancing Nigerian Federal System: The Politics and Economics of a Federation. - Fadakinte, M. M.; Abdulkareem, Musa (Advances in Social Sciences Research Journal, 2020)
This paper discusses the efforts that have been made since Nigeria became independent in 1960 to balance her federal system. These efforts include balancing the territorial structure, creation of states, the power structure between the central and state governments, balancing inform of revenue allocation formulae and balancing by the adoption of federal character principle. Thus, to what extent have these efforts succeeded in balancing Nigerian federal system? Today, however, the efforts continue as Nigerian federal system is being confronted by the clamour for restructuring. The paper concludes by recommending a review of the current federal system which is being practiced more like a unitary system.